2018
DOI: 10.1039/c8ob02713g
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of the potent anti-inflammatory natural product solomonamide A along with structural revision and biological activity evaluation

Abstract: Herein, we report the total synthesis of solomonamide A along with its structural revision for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…In the last years, different studies toward the synthesis of solomonamides have been reported, mainly by Reddy et al [15,17,37,38,39,40,41]. In fact, very recently, the total syntheses of solomonamides A and B have been reported [13], which led to their stereochemical revision with respect to that initially proposed, and confirmed the anti-inflammatory activities reported for the natural products.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In the last years, different studies toward the synthesis of solomonamides have been reported, mainly by Reddy et al [15,17,37,38,39,40,41]. In fact, very recently, the total syntheses of solomonamides A and B have been reported [13], which led to their stereochemical revision with respect to that initially proposed, and confirmed the anti-inflammatory activities reported for the natural products.…”
Section: Discussionmentioning
confidence: 75%
“…Such is the case of the potent anti-inflammatory octacyclopeptides perthamides [8,9] and swinholides, with antifungal effect [10] and antiproliferative activity against a number of tumor cells by the disruption of actin cytoskeleton [11]. Together with them, solomonamide A ( 1 ) and B ( 2 ) are two bioactive compounds that have been recently isolated from T. swinhoei and described as exerting a dose-dependent anti-inflammatory activity in vivo [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iriomoteolide-2a Incorrect stereochemistry [30,31 ] Incorrect stereochemistry [26] Anabaenopeptin Incorrect stereochemistry [30,31 ] Incorrect stereochemistry [27] Anabaenopeptin Incorrect constitution [34] Xanthone Chemical derivatization…”
Section: Meroditerpenementioning
confidence: 99%
“…Here we are reporting syntheses of all possible stereoisomers of solomonamide B macrocycles particularly around AHMOA fragment keeping the alanine stereocenter fixed. Among these, two macrocycles with 2 S , 3 R , 4 R and 2 S , 3 S , 4 S stereochemistry were previously synthesized in our lab during the stereochemical revision of natural products . Synthesis of the remaining six possible stereoisomers is a challenging task and involves remodelling of the synthetic pathways.…”
Section: Introductionmentioning
confidence: 99%